Efficacy of transanal tube placement after anterior resection for rectal cancer: a systematic review and meta-analysis. Issue 1 (December 2016) - Wang, Shuanhu; Zhang, Zongbing; Liu, Mulin; Li, Shiqing; Jiang, Congqiao
Abstract Background Anastomotic leakage is a serious complication that can occur after anterior resection of the rectum. There is a question regarding whether the placement of a transanal tube can decrease the rate of anastomotic leakage. The aim of this systematic review and meta-analysis was to evaluate the efficacy of transanal tube placement after anterior resection. Methods We searched three major databases (PubMed, Embase, and the Cochrane Library) up until January 2015 for studies evaluating the benefit of transanal tubes after anterior resection for rectal cancer. The primary outcome measure was the rate of clinical anastomotic leakage. Secondary outcome was the rate of reoperation. Pooled risk ratios (RR) with 95 % confidence intervals (CI) were obtained using random effects models. Results One randomized controlled trial and three observational studies involving 909 patients met inclusion criteria. Clinical anastomotic leakage occurred in 3.49 % (14 of 401) of patients with transanal tubes and 12.01 % (61 of 508) of patients without transanal tubes. Meta-analysis of the studies showed a lower risk of anastomotic leakage (RR, 0.32; 95 % CI 0.18–0.58) and reoperation related to leakage (RR, 0.19; 95 % CI 0.08–0.46) when the transanal tube was placed. Conclusions While studies are few and mostly observational, the data to date indicate that placement of a transanal tube decreases the rate of clinical anastomotic leakage and reoperation related to leakage. More studies are needed to confirm these findings.